Valoración del uso de bacterias nitrificantes para el control de nitritos en cultivos intensivos de camarón (litopenaeus vannamei ). - Coronel Ordoñez, Gwen Ibeth; Campoverde Romero, Erick David (Machala : Universidad Técnica de Machala, 2024)
The use of nitrifying bacteria for nitrite control in intensive shrimp cultures represents a sustainable strategy to improve water quality. In this study, the efficiency of probiotic products composed of Nitrosomonas and Nitrobacter in reducing nitrites in intensive aquaculture systems was evaluated. Sediment and water were collected from a freshly harvested pool at the FRANMAR shrimp farm (Huaquillas) and a completely randomized experiment was designed with three treatments and three replications. The treatments included a control without the addition of bacteria (TC), a treatment with a concentration of 20 billion CFU/g (T1) and another with 1300 billion CFU/g (T2). Ammonia, nitrite, dissolved oxygen and pH measurements were made three times a day. The results showed that the application of nitrifying bacteria significantly reduced nitrite levels, with a greater impact in the treatment with a higher bacterial concentration. No significant variations in pH were observed, but the bacteria treatments maintained higher dissolved oxygen levels compared to the control. Nitrite reduction started on Day 4 in T2 and on Day 5 in T1, being completed on Day 7 and 8, respectively. And regarding OM reduction, nitrifying bacteria managed to reduce it by 61% in all treatments. These findings highlight the importance of bacterial concentration to optimize water quality and improve the sustainability of aquaculture systems.
El uso de bacterias nitrificantes para el control de nitritos en cultivos intensivos de camarón representa una estrategia sostenible para mejorar la calidad del agua. En este estudio, se evaluó la eficiencia de productos probióticos compuestos por Nitrosomonas y Nitrobacter en la reducción de nitritos en sistemas acuícolas intensivos. Se recolectó sedimento y agua de una piscina recién cosechada de la camaronera FRANMAR (Huaquillas) y se diseñó un experimento completamente al azar con tres tratamientos y tres repeticiones. Los tratamientos incluyeron un control sin adición de bacterias (TC), un tratamiento con una concentración de 20 billones de UFC/g (T1) y otro con 1300 billones de UFC/g (T2). Se realizaron mediciones de amoníaco, nitritos, oxígeno disuelto y pH tres veces al día. Los resultados demostraron que la aplicación de bacterias nitrificantes redujo significativamente los niveles de nitritos, con un mayor impacto en el tratamiento con mayor concentración bacteriana. No se observaron variaciones significativas en el pH, pero los tratamientos con bacterias mantuvieron niveles más altos de oxígeno disuelto en comparación con el control. La reducción de nitritos comenzó en el Día 4 en T2 y en el Día 5 en T1, completándose en el Día 7 y 8, respectivamente. Y en cuanto a la reducción de MO, las bacterias nitrificantes lograron reducir un 61% en todos los tratamientos. Estos hallazgos resaltan la importancia de la concentración bacteriana para optimizar la calidad del agua y mejorar la sostenibilidad de los sistemas acuícolas.
Keywords: BACTERIAS NITRIFICANTES; CULTIVOS INTENSIVOS; NITRITOS